Methodology in EAP: still an overlooked issue? - Bell, Douglas (N/A, 2021)
In 2003 it was suggested that insufficient attention had been paid to methodology and pedagogy in EAP and that there had been an over-emphasis on the ‘what’ at the possible expense of the ‘how’. While conferences and other professional events have gone some way towards addressing this issue, in terms of EAP journal outputs, as a survey of the Journal of English for Academic Purposes (JEAP) shows, not very much seems to have changed. The pages of JEAP still suggest a dearth of research interest in issues related to EAP methodology. This reflective paper argues that much greater prominence needs to be given to pedagogical matters in EAP, not least because teaching still accounts for the bulk of what most EAP practitioners do. The paper further suggests that the transfer of methodology and pedagogy from General ELT to EAP should be considered more critically than has hitherto been the case.